The Doklam Standoff and Importance of Strategic Border Infrastructures: A Critical Analysis from the National Security Perspective of India, China, and Bhutan - Paudel, Bhuwan (KTFT Journal, 2024)
Bhutan is a small landlocked and even in the 21st century self-isolated country located between the world's most populous neighbors i.e. India and China. Though it has long association and affinities with Tibet’s history, culture, and way of living, Bhutan has no formal diplomatic relations with its vicinity neighbor People’s Republic of China. But interestingly it adher5s to the One China Policy. This paper is trying to gain a deeper understanding about Bhutan’s relations with China and what exactly the border problem it has with China. In a similar vein, it also looks at why India actively engages in Sino-Bhutan border disputes without a formal request from Bhutan. Based on the available resources and various constraints for getting sufficient information, hermeneutic methodology has been applied. The paper also highlighted the strategic importance of the Doklam for trio countries and why strategic border infrastructures are remained priority which caused tussles in the relations of neighborhood relations.